PENGARUH PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE COOPERATIVE INTEGRATED READING AND COMPOSITION DALAM PENINGKATAN HASIL BELAJAR PENDIDIKAN PANCASILA PESERTA DIDIK KELAS IV - Rani Selvia; Dayu Rika Perdana; Roy Kembar Habibi; Herpratiwi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the low learning outcomes in Pancasila Education among fourth-grade elementary school students, which were caused by limited student participation and the dominance of teacher-centered learning approaches. The purpose of this study was to determine the effect of the Cooperative Integrated Reading and Composition (CIRC) learning model on improving students’ learning outcomes in Pancasila Education at SD Negeri 1 Bangunrejo. This research employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The participants consisted of 49 fourth-grade students, including 24 students in the experimental class and 25 students in the control class. Data were collected through pretests and posttests, observations, interviews, and documentation. Data analysis included normality testing, homogeneity testing, N-Gain analysis, and simple linear regression. The findings revealed that the average score of students in the experimental class increased from 61.04 to 79.79, while the control class increased from 61.80 to 74.40. Hypothesis testing showed a significance value of 0.000 (< 0.05) with an F-value of 322.573, indicating that the CIRC learning model had a significant effect on students’ Pancasila Education learning outcomes. These findings contribute to the advancement of educational science by providing empirical evidence regarding the effectiveness of cooperative learning models in enhancing learning outcomes, student engagement, and collaborative skills at the elementary school level.